Desafios e possibilidades do sistema de garantia de direitos à população migrante no município de Porto Alegre - Bosner, Beatriz de Moraes Vieira (2020)
The objective of this dissertation is to analyze how the system of guaranteeing the human rights to the migrant population in the city of Porto Alegre has been constituted, in order to identify the challenges and possibilities for the realization and the defense of the human rights of this social segment. It was instituted as a qualitative, descriptive and exploratory study, based on Marx's critical dialectical method. For data collection, we used documentary and bibliographic sources, as well as semi-structured interviews with seven professionals from the defense, control and promotion of the rights guarantee system to the migrant population of Porto Alegre. The analysis of the results obtained was succeeded by content analysis in Bardin. The results achieved made it possible to unveil the reality of the system of guaranteeing rights to migrants from Porto Alegre, demonstrating the (un) protective and (un) responsible character that the state has with this social segment in view of the neoliberal conjuncture. Due to the context of precariousness and exhaustion that the institutions and public policies of the rights guarantee system have been suffering, the actions developed by the public services are insufficient to meet all the complex demands and needs of the migrant population. Through this situation, there is the strengthening of civil society actions on the theme of migration, through the assistance, focus and humanitarian nature, as well as partnerships between the public and private sectors. Although in the context of the dismantling of rights, numerous barriers and daily challenges to the implementation of the rights guarantee system are identified, there are also strategies and possibilities of resistance to the processes that violate the rights of migrants, such as the strengthening of rights. spaces of social control, intersectoral articulation between services, effort in action planning, among other issues.